COVID-19: Does it Affect Maternal Anxiety and Maternal Fetal Bonding? - Şenkaya, Ayşe Rabia; Gürcan, Mehmet Buğrahan; Aytaç, Hakkı (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of this study was to examine pregnant women, who are a mentally sensitive group, in terms of anxiety level, prenatal attachment, thought content, and demographic characteristics in the COVID-19 pandemic where quarantine rules are applied. Methods: Our study is a cross-sectional study. In the first peak of the pandemic, 204 pregnant women with a gestational period ranging from 20 to 40 weeks who visited our hospital on an outpatient basis between April 2020 and June 2020 voluntarily participated in our study. A demographic data form, Generalized Anxiety Disorder-7 (GAD-7) test, Prenatal Bonding Inventory, and COVID-19-related questionnaire were given to these pregnant women. The women were divided into 2 groups as anxious and non-anxious, and the results were compared. Results: According to the Generalized Anxiety Disorder-7 test, 36.3% (n = 74) of the pregnant women were found to be anxious. Significant differences were found between the 2 groups in the scores of the Prenatal Bonding Inventory, Generalized Anxiety Disorder-7, and COVID-19-related questionnaire (question 1, question 2, question 4, and question 5) (P < .05). There was a positive correlation between the scores of the GAD-7 scale and the Prenatal Bonding Inventory scores which were used to measure the anxiety level of pregnant women, and the Prenatal Bonding Inventory scores of the anxious group were significantly higher than those of the non-anxious group, resulting in the view that prenatal anxiety increased bonding. Conclusions: Our study supported the fact that the COVID-19 pandemic causes anxiety in pregnant women, but it shows that this anxiety increases the level of maternal–fetal bonding. Cite this article as: Şenkaya AR, Gürcan MB, Aytaç H. COVID-19: Does it affect maternal anxiety and maternal fetal bonding? Cerrahpaşa Med J. 2022;46(3):263-268.